2009
DOI: 10.1007/s00125-009-1515-4
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and histological effects of exendin-4 (exenatide) on the rat pancreas

Abstract: Aims/hypothesis Exendin-4 is a 39 amino acid agonist of the glucagon-like peptide receptor and has been approved for treatment of type 2 diabetes. Many reports describe an increased incidence of acute pancreatitis in humans treated with exendin-4 (exenatide). Previous studies have evaluated the effect of exendin-4 on beta cells and beta cell function. We evaluated the histological and biochemical effects of exendin-4 on the pancreas in rats. Methods We studied 20 Sprague-Dawley male rats, ten of which were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
152
3
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(165 citation statements)
references
References 17 publications
7
152
3
1
Order By: Relevance
“…There was a nonsignificant difference in duct cell proliferation after 6 weeks of treatment. These observations and the findings of other studies [27][28][29][30][31][32] raise the issue of whether GLP-1-based therapies are a potential risk for pancreatitis; some studies did not observe this effect [33,34], however, which may reflect the animal model used, the age of the animals and/or the labelling and counting methods used for proliferating cells. In our study, there was no indication of a systemic inflammatory state.…”
Section: Discussionmentioning
confidence: 86%
“…There was a nonsignificant difference in duct cell proliferation after 6 weeks of treatment. These observations and the findings of other studies [27][28][29][30][31][32] raise the issue of whether GLP-1-based therapies are a potential risk for pancreatitis; some studies did not observe this effect [33,34], however, which may reflect the animal model used, the age of the animals and/or the labelling and counting methods used for proliferating cells. In our study, there was no indication of a systemic inflammatory state.…”
Section: Discussionmentioning
confidence: 86%
“…As a consequence thereof, the statistical power is low. Three of the four studies that have described adverse effects of DPP-4is or GLP-1RAs on the pancreas were performed in rodents (15,25,26). Thus, at the current point in time with the very few studies available in nonhuman primates, the cumulative data in these studies have a strong relevance for the assessment of adverse pancreas effects in humans, despite the relatively limited number of animals per group.…”
Section: Discussionmentioning
confidence: 99%
“…The four studies that have suggested adverse effect of DPP-4is or GLP-1RAs on the pancreas have described or discussed increased risk for pancreatitis, metaplasia, or inflammation and pancreatic adenocarcinomas and glucagonomas (15,16,25,26). In contrast, hundreds of other studies have investigated effects of these drugs on the pancreas but have not reported adverse effects; a few are referenced here for liraglutide (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated in a literature review that new islets do develop under certain experimental conditions, such as after partial pancreatectomy, where the formation of new islets has been clearly demonstrated (Nachnani et al, 2010). Other anatomical structures, such as kidney glomeruli, also lack the ability of hyperplasia and instead become hypertrophic with an increased demand, probably because of the highly specific structure of the neurovascular and tubular systems necessary for appropriate function.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of numerous experimental studies about EX-4 effects on various tissues in non-diabetic subjects, only one study has investigated its effects on the pancreas (Nachnani et al, 2010). In the present study, the effect of EX-4 on islet volume and number in the mouse pancreas was investigated by using stereological procedures.…”
Section: Introductionmentioning
confidence: 94%